Media coverage of evidence outputs during the COVID-19 pandemic: findings from one national agency. (20th October 2021) - Sharp, M; Forde, Z; McGeown, C; O'Murchu, E; Smith, SM; O'Neill, M; Ryan, M; Clyne, B
Abstract: Background: The COVID-19 Evidence Synthesis Team within the Health Information and Quality Authority (HIQA) in Ireland produced a range of evidence-based reports on a broad range of public health topics related to COVID-19. These evidence outputs (EO) arose directly from questions posed by policy makers and clinicians supporting Ireland's National Public Health Emergency Team (NPHET). Findings from these EOs informed the national response to the COVID-19 pandemic in Ireland and influenced international public health guidance. How research findings are presented through domestic news can influence behaviour and risk perceptions. Methods: We investigated traditional media coverage of nine COVID-19 EOs and associated press releases, published (April to July 2020) by HIQA. NVivo was used for conceptual content analysis of manifest content. 'Core messages' from each evidence output were proposed and 488 sources from national and regional broadcast, print, and online media were coded at the phrase level. The presence of political and public health actors in coverage were also coded. Results: Coverage largely did not distort or misrepresent the results of the EOs, however, there was variability in terms of what content was reported on and to what extent different stakeholders were involved in the contextualization of the findings of the EOs. Coverage appeared to focus more on 'human-interest' stories as opposed to more technical reports (e.g. focusing on viral load, antibodies, testing, etc.). Selective reporting and the variability in the use of quotes from governmental and public health stakeholders changed and contextualized results in different manners than perhaps originally intended in the press release. Conclusions: Our findings provide a case-study of European media coverage of evidence reports produced by a national agency. Results highlighted several strengths and weaknesses of current communication efforts.